CFD analysis of a SD 7003 airfoil with a local correlation based transition and turbulence model - Islam, Mazharul; Langfeldt, Felix; Fürst, Jiri; Wood, David H. (IOP Publishing, 2017)
The SD 7003 has been investigated quite extensively in the past at different Reynolds numbers. At moderate Reynolds numbers and low angles of attack its upper surface is dominated by a large laminar separation bubble which provides a demanding test case for RANS-based transition models. In this article, a widely used open-source Computational Fluid Dynamics (CFD) toolbox has been used mainly to investigate the (i) aerodynamics coefficients and (ii) boundary layer transitional behaviors of a SD 7003 airfoil using a local correlation-based γ – Reθt SST [1] transition and turbulence model. Several researchers have proposed different correlations which can be used in the γ – Reθt SST. In this article, five such correlations have been investigated for the SD 7003 at low Reynolds number which is particularly challenging for CFD analysis.